Impact of remittances on fertility - George Naufal (IZA World of Labor, 2015)
The growth in the number and in the size of remittances and the stability of these monetary transfers have made them a prime target for policymakers. Because remittance flows go directly to households in emigrants' home countries, one has to wonder about their effects on household decision-making, particularly in relation to the number of children to have. While this is household specific, when considered at the community and country level, there are significant policy implications for remittance-receiving economies. Therefore, it is crucial to more fully understand the relationship between remittance inflows and fertility rates.
Keywords: F22; F24; J13; O15; 330; migration; remittances; fertility; developing economies; economic development